KOTAK SAMPAH OTOMATIS BERBASIS ARDUINO MEGA 2560 - Reza Mahendra; Irma Salamah; Nasron Nasron (Universitas Islam Balitar Blitar, 2020)
Environmental Cleanliness still have low public attention. Public tends to inapropriately littering which caused by the trash bin is in full capacity. This things happened because the lack of monitoring by the janitor. The problem mentioned before can be overcome by designing an automatic monitoring system without being monitored all time and send notification. This research will design an automatic trash bin which will send notification of SMS upon reaching full capacity. This trash bin is equipped with Arduino Mega 2560, SIM 900 module, and infrared. This research will be implemented for a better quality of environmental protection.